Standarisasi Eksrtak Etanol 96% Daun Cantigi (Vaccinium varingiaefolium Miq.) - Yulius Evan Christian; Deni Rahmat; Yunahara Farida (Fakultas Farmasi Universitas Pancasila, 2022)
Advantages of Cantigi (Vaccinium varingiaefolium Miq.) include anti-inflammatory, Spasmolytic, Antiviral, and Hypotensive Properties. The objective of this study was to standardize the Cantigi leaf extract. Non-specific parameters include total ash content, acid insoluble ash content, water content, dry loss, determination of heavy metals (Hg, As, Cd, Pb, hydroquinone), mold number, yeast, total plate count, and solvent residue. Specific parameters included extracts soluble in ethanol and water. Cantigi leaves are extracted by kinetic maceration using solvents such as n-hexane, ethyl acetate, and 96% ethanol. To obtain a thick extract, 96% ethanol extract was evaporated using a rotary evaporator. The experiment produced 44.5 g of the cantigi leaf extract in 96% ethanol. Phytochemical screening presents alkaloids, saponins, tannins, flavonoids, triterpenoids, steroids, essential oils, and quinones. Ethanol soluble extract was 9.49% and that of the water-soluble extract was 22.21%. A total of ash 3.66%, an acid insoluble ash 0.35%, water content 6.31%, and drying loss 6.49%. Results of the heavy metal contamination test revealed that no traces of Hg, As, Cd, Pb, or hydroquinone were found, along with 10 yeast molds, 10 plates, and 0.005% residual ethanol solvent. Based on the results, cantigi leaf extract met the standard of extract quality.